EDUKASI KEKASIH (KENALI, KENDALIKAN, DAN CEGAH HIPERTENSI) PADA LANJUT USIA DALAM UPAYA PENCEGAHAN HIPERTENSI - Hanna Mutiara; Muhammad Ricky Ramadhian; Nimeyer Yehezkiel; Liza Anggraeni; Anisa Amelia; Salista Salista; Mira Dwi Utami; Sheliyana Cahya Oktari; M. Mukhlis Dalimunte (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
Hypertension remains one of the leading non-communicable diseases and continues to pose a significant public health challenge. Limited public knowledge regarding its risk factors, prevention, and management contributes to the high prevalence of uncontrolled hypertension. This community service program aimed to improve older adults' knowledge of hypertension through the KEKASIH (Know, Control, and Prevent Hypertension) program, which integrated health education and basic health screening. The activity was conducted at the Older Adults Integrated Health Service Post (Posyandu Lansia) in Tanjung Raja Sakti Village, Blambangan Umpu District, Way Kanan Regency, Lampung Province, Indonesia. The participants included community health volunteers and older adults attending the community health service, with a total of 17 participants. Program effectiveness was evaluated using pre-test and post-test assessments. The findings demonstrated a substantial improvement in participants' knowledge following the intervention. The mean knowledge score increased from 51.06 in the pre-test to 81.54 in the post-test. Furthermore, the proportion of participants with good knowledge increased from 17.65% to 64.71%, while those with poor knowledge decreased from 35.29% to 11.76%. These findings indicate that the KEKASIH program effectively enhanced older adults' knowledge of hypertension, emphasizing the importance of early detection and the adoption of healthy lifestyle behaviors. Integrating health education with health screening and collaboration with primary healthcare centers has the potential to serve as a sustainable health promotion and disease prevention strategy for hypertension control at the community level.